Pengaruh Edukasi Kesehatan Fisik Tentang COVID-19 Terhadap Kemampuan Menerapkan AKB Pada Siswa SD - Linda Sari Barus; Susanti Niman; Tina Shinta Parulian Siahaan; Ira Ocktavia Siagian (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Covid-19 pandemic is a non-natural disaster. Everyone, including children, becomes stressed, to prevent transmission of the virus, an adaptation of new habits is needed, so it is necessary to provide knowledge in the form of repeated education related to new normal adaptation to improve physical health. This is necessary so that the child's ability to apply the new normal adaptation is consistent. This new normal adaptation is a necessary step to determine the readiness of elementary school children to conduct limited face-to-face learningMethods: This article used a pre-experimental design, namely by means of a one-group pre-test-post-test design for 73 elementary school students in Bandung. The child is given a pre-test regarding the new normal adaptation and then a video is given about physical health that must be considered in the new normal adaptation, after which a post-test assessment is carried out. Bivariate Analysis Using the Wilcoxon test. Results: The results of the study found that there was an influence before being given physical health education about covid-19 on the ability of elementary school students to implement the new normal adaptation. Conclusion: Researchers suggest parents and teachers to keep reminding their children to adapt to new habits.